Ambulatory Assessment of Psychological and Physiological Stress on Workdays and Free Days Among Teachers. A Preliminary Study - Wettstein, Alexander; Kühne, Fabienne; Tschacher, Wolfgang; La Marca, Roberto (Frontiers in Neuroscience, 2020)
Objective: Teachers are affected by high levels of job stress, leading to one of the highest rates of burnout. The purpose of our pilot study was to investigate the diurnal course of teachers’ psychological and physiological stress responses (cortisol levels, alpha-amylase, heart rate, and heart rate variability). Another aim of the project was to test the applicability of ambulatory assessment methods in daily teaching situations. Methods: In a non-clinical sample of eight primary school teachers (mean age = 43, SD = 15.22, 6 females) in Switzerland, continuous biopsychological data on two workdays and a free day were assessed. The teachers’ heart rates (HRs) and heart rate variability (HRV) were measured continuously using an ambulatory ECG. Additionally, eight saliva samples were collected from the teachers repeatedly throughout the day to determine the diurnal course of salivary cortisol and alpha-amylase (sAA). Perceived stress and anger ratings were assessed simultaneously. Results: As hypothesized, the teachers’ morning cortisol levels, perceived stress, and anger levels were significantly higher, and their overall HRV was significantly lower on workdays than on a free day. Conversely, sAA levels and HRs showed no significant differences between working and free days. Salivary markers exhibited the expected diurnal course, with decreasing cortisol and increasing sAA levels over the course of the day, while self-rated stress reached the maximum at midday during working days. Conclusions: The results of the present explorative study show that physiological and psychological parameters differ within working and free days for teachers. A comparison between working and free days resulted in differences in morning cortisol levels, heart rate variability as well as stress and anger levels. The ambulatory assessment method was found to be applicable in daily teaching situations.